Pengaruh Prestasi Belajar Akidah Akhlak Terhadap Karakter Siswa Di MTs Muhammadiyah Tempurrejo Ngawi - Anti Mabruroh; Nining Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2021)
In this modern era is accompanied by a fairly rapid advance in science as students' character tends to decrease because of the ease and freedom of students accessing various types of information. This makes it easier for foreign cultures to enter the country and affect the nation's character. This study aims to determine: 1. Achievement of learning aqidah akhlaq students; 2. Student character; 3. Effect of learning achievement aqidah akhlaq on student character. This research is a quantitative study with a set of correlation approaches. The location of this study in MTs Muhammadiyah Tempurrejo Ngawi with a population of 170 students. The research sample of 53 students were selected using purposive sampling. Data obtained through questionnaire tests and see the value of students' odd semester report cards. Meanwhile, instrument testing uses validity test, reliability test, analysis prerequisite analysis uses normality test, independent test, and linearity test while data analysis techniques of data analysis use correlation analysis techniques and regression analysis techniques to determine the dependent variable of the independent variable. Based on research concluded that MTs Muhammadiyah Tempurrejo Ngawi in 2019/2020, it can be concluded that: (1) student achievement is included in both categories with an average value of 92; (2) students' characters are included in both categories with an average rating of 91; (3) there is a significant influence between the learning achievement of aqidah akhlaq on the character of students in MTs Muhammadiyah Tempurrejo and the results of data calculation using T-test. The results of t count> t table are 19.497> 2.00758 at the 5% significance level and 19.497> 2.67572 at the 1% significance level. So it can be concluded to be hypothesis is accepted which means that there is a significant influence between the moral learning achievements of aqidah Akhlaq on student characters.